Potensi Pendapatan Retribusi Pengolahan Lumpur Tinja di IPLT Talang Bakung, Kota Jambi, Provinsi Jambi - Prayudi, Tibin Ruby (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2014)
The Talang Bakung Septic Sludge Treatment Plan with the treated capacity of 80 m/m3 is provided to treat the septic sludge of the Community of Jambi City. The Septic Treatment that is operatied since 1996 has not properly functions. This research is aimed to assess the potential benefit of retribution from the financial, economic and environmental aspects. This income retribution is calculated based on desludged eKKiciency of 30%, 50%, 60% and 100% of the treatment capacity of the two yearly desluging Septic Tank. The research concluded that the potential income retribution with 30%-100% desludging efeiciency is IDR 683.341.200 up to IDR 2.127.804.000. Based on that income potential, the desludging tariKK is IDR 136.300 per m3 of desludged sludge. Meanwhile, the existing tariKK is IDR 100.000 per m3 of desludged sludge. This situation causing lost of environmental economic value that is equal to 0,5% of the existing Bank interest rate of 18%/year.